The Itivuttaka. Translated by Peter Masefield. - Norman, K. R. (Buddhist Studies Review, 2001)
The Itivuttaka. Translated by Peter Masefield. Pali Text Society, Oxford 2000. xv, 125 pp. £12.00. ISBN 0 86013 386 9.